Food in the Book «HACE TIEMPOS» by Tomás Carrasquilla. An Overview of Antioquian Cuisine from below in Times of Modernisation, 1870-1930 (2023)
This article relates Antioquian cuisine with the modernization process that was taking place in the late 19th century. Using methodological resources from people’s history and subaltern studies, it seeks to unveil how ordinary people incorporated ideas of change and resistance in a society experiencing the first effects of modernisation. Food, from Claude Lévi-Strauss to Massimo Montanari, has been considered an object of structured study with a «grammar», or conventions, that give it order, meaning, and cultural and social significance. This has motivated the question: «To what extent did the modernisation process modify that structure and grammar of food?» The article conducts a literary and semiotic analysis of the three volumes of the work Hace tiempos by the costumbrist writer Tomás Carrasquilla, which is rich in details about Antioquian popular culture. First, it analyses the people’s history category according to Carrasquilla's work. Then, it examines the concept of cuisine as a creator of identities, its identification in the work, and its relationship with the modernising project. Finally, it defines the terms of the tension between popular cuisine and haute cuisine.